Implementasi Strategi Pengawasan Komisi Penyiaran Indonesia (KPI) terhadap Program Televisi dalam Mewujudkan Siaran Ramah Anak - Agustina, Maulidya; Hermawan, Dedy; Prihantika, Ita (Jurnal Analisis Sosial Politik, 2020)
Children's programs currently served are not in accordance with the classification of programs during children's broadcast hours and children's content that contains violence and contains more foreign animation than local children's shows. Therefore, Komisi Penyiaran Indonesia (Indonesian Broadcasting Commission), which was formed as an independent institution, has the authority to compile and supervise various broadcasting regulations that connect broadcasting institutions requiring a strategy in monitoring television programs in realizing child-friendly broadcasts. This study aims to describe and analyze the implementation of the strategy of Komisi Penyiaran Indonesia in monitoring television programs to achieve child-friendly broadcasts. This research was conducted with a descriptive qualitative approach. Data collection was carried out by interview, documentation and observation. The results of this study indicate that the implementation of the strategy of Komisi Penyiaran Indonsia is quite good but there are still shortcomings in the budget and target recipients, namely broadcasting institutions that are still committing violations. The implementation strategy is formulated into a program, in the form of Bimbingan Teknis Penyiaran Anak, Anugerah Penyiaran Ramah Anak and Pengaturan Isi Siaran Anak.